Lektury lekarza – książka Leonarda Botalla w Bibliotece Uniwersyteckiej w Poznaniu - Wilgosiewicz-Skutecka, Renata; Szulc, Alicja (Biblioteka Uniwersytecka w Poznaniu, 2009)
Wśród druków francuskich Biblioteki Uniwersyteckiej w Poznaniu znajduje się interesujący zbiór (klocek) szesnastowiecznych traktatów medycznych, wydany w Lyonie przez Guillaume’a Rouillé oraz Paula Miraillet, zawierający dwa dzieła Galena: De naturalibus facultatibus libri tres (1548) i De bono et malo succo, liber unus (1547) oraz traktat Donato Antonio Altomare De alteratione, concoctione, digestione, praeparatione, ac purgatione: ex Hippocratis et Galeni sententia methodus (1548). Wolumin ten należał do Leonarda Botalla (1519-1587), włoskiego anatoma i chirurga, medyka królów francuskich, i nosi ślady jego lektury – liczne marginalia, podkreślenia i komentarze w języku łacińskim. Pobieżna analiza tego materiału rękopiśmiennego, zwłaszcza wielu krytycznych uwag Botalla wobec poglądów Galena, pozwala widzieć w tych zapiskach świadectwo przemian zachodzących w medycynie w XVI wieku, która dopiero w tym okresie stała się nauką w pełni nowożytną. Przedstawiona w niniejszym artykule ogólna charakterystyka woluminu jest jedynie wprowadzeniem do szczegółowej analizy zapisków Leonarda Botalla, która pozwoliłaby historykom medycyny dokładniej zrekonstruować poglądy lekarza z Asti, będące świadectwem recepcji dzieł Galena w XVI wieku i toczącej się wokół nich dyskusji.

The French section of the old and rare books department of Poznań University Library includes an interesting collection (bound volume) of the sixteenth century medical treatises published by Guillaume Rouillé and Paul Miraillet in Lyon that consists of two works by Galen: De naturalibus facultatibus libri tres (1548) and De bono et malo succo, liber unus (1547) as well as a treatise written by Donato Antonio Altomare: De alteratione, concoctione, digestione, praeparatione, ac purgatione: ex Hippocratis et Galeni sententia methodus (1548). The bound volume once belonged to Leonardo Botallo (1519-1587), an Italian anatomist and surgeon, court doctor to French kings. The text bears signs of his reading – there are numerous glosses on margins, underlined lines and hand-written comments in Latin. Even a cursory analysis of the notes (glosses), of Botallo’s critical remarks on Galen’s part in particular, allows us to examine the manifestation of the changes going on in medicine of the sixteenth century, i.e. the time when it reached a phase of being a fully-fledged modern branch of science. The presented general characteristics of the volume only makes an introduction to a more detailed study on the notes by Leonardo Botallo. Further studies would allow historians in medicine to reconstruct the views and opinions of the doctor from Asti in Piedmont that can testify to the attitude towards and approach to Galen’s work in the sixteenth century and to the contemporary debate surrounding their reception.
The assigned reading of the physician – Leonardo Botallo’s book in the collection of Poznań University Library
Keywords: Leonardo Botallo; Galenizm; medycyna XVI wieku; 16th century medicine galenism; stare druki; old prints; Biblioteka Uniwersytecka w Poznaniu; Poznań University Library